Medicinal plant Miconia albicans synergizes with ampicillin and ciprofloxacin against multi-drug resistant Acinetobacter baumannii and Staphylococcus aureus - Genilson Silva de Jesus; Danielle Silva Trentin; Thayná Fernandes Barros; Alda Maria Teixeira Ferreira; Bruna Castro de Barros; Patrícia de Oliveira Figueiredo; Fernanda Rodrigues Garcez; Érica Luiz dos Santos; Ana Camila Micheletti; Nidia Cristiane Yoshida (BMC, 2023)
Abstract Background Given the rising occurrence of antibiotic resistance due to the existence and ongoing development of resistant bacteria and phenotypes, the identification of new treatments and sources of antimicrobial agents is of utmost urgency. An important strategy for tackling bacterial resistance involves the utilization of drug combinations, and natural products derived from plants hold significant potential as a rich source of bioactive compounds that can act as effective adjuvants. This study, therefore, aimed to assess the antibacterial potential and the chemical composition of Miconia albicans, a Brazilian medicinal plant used to treat various diseases. Methods Ethanolic extracts from leaves and stems of M. albicans were obtained and subsequently partitioned to give the corresponding hexane, chloroform, ethyl acetate, and hydromethanolic phases. All extracts and phases had their chemical constitution investigated by HPLC-DAD-MS/MS and GC-MS and were assessed for their antibiofilm and antimicrobial efficacy against Staphylococcus aureus. Furthermore, their individual effects and synergistic potential in combination with antibiotics were examined against clinical strains of both S. aureus and Acinetobacter baumannii. In addition, 10 isolated compounds were obtained from the leaves phases and used for confirmation of the chemical profiles and for antibacterial assays. Results Based on the chemical profile analysis, 32 compounds were successfully or tentatively identified, including gallic and ellagic acid derivatives, flavonol glycosides, triterpenes and pheophorbides. Extracts and phases obtained from the medicinal plant M. albicans demonstrated synergistic effects when combined with the commercial antibiotics ampicillin and ciprofloxacin, against multi-drug resistant bacteria S. aureus and A. baumannii, restoring their antibacterial efficacy. Extracts and phases also exhibited antibiofilm property against S. aureus. Three key compounds commonly found in the samples, namely gallic acid, quercitrin, and corosolic acid, did not exhibit significant antibacterial activity when assessed individually or in combination with antibiotics against clinical bacterial strains. Conclusions Our findings reveal that M. albicans exhibits remarkable adjuvant potential for enhancing the effectiveness of antimicrobial drugs against resistant bacteria.